2014
DOI: 10.1080/02680939.2014.924562
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of students’ unions within contemporary higher education

Abstract: Despite profound changes to the higher education sector in the UK over recent years, which have tended to emphasise the role of prospective students as active choosers within a marketplace and encourage higher education institutions to place more emphasis on student engagement and representation as a means of improving the quality of the learning experience, the role of students' unions has remained largely unexplored. To start to redress this gap, this paper draws on a UK-wide survey of students' union office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 19 publications
2
62
0
1
Order By: Relevance
“…The Office for Students (comprised mainly, of non-students) is seen as a more effective means of representing the 'student voice' than elected student representatives. While research has suggested that, in contemporary UK higher education, institutional students' unions rarely take an oppositional stance, and can often be very supportive of university management agendas (Brooks, Byford, and Sela 2015), it appears that they are still viewed with suspicion by policy-makers.…”
Section: Political Actorsmentioning
confidence: 99%
“…The Office for Students (comprised mainly, of non-students) is seen as a more effective means of representing the 'student voice' than elected student representatives. While research has suggested that, in contemporary UK higher education, institutional students' unions rarely take an oppositional stance, and can often be very supportive of university management agendas (Brooks, Byford, and Sela 2015), it appears that they are still viewed with suspicion by policy-makers.…”
Section: Political Actorsmentioning
confidence: 99%
“…Institutional staff have the choice as to whether to attend to those views or not, and to avoid seeking student opinion on matters which they consider students to have little to contribute. This type of student engagement is situated as merely one of numerous systems by which students express opinions and raise issues, rather than a vehicle for critical dissent or challenge (Brooks et al 2014). Through these formal feedback and representation systems students could, in principle, raise wider issues about the university community in those spaces, but while these are framed in terms of raising issues and feeding back on pre-defined categories, there is limited likelihood that they will do so spontaneously.…”
Section: Student Engagement In the Formation Of Communities As Consulmentioning
confidence: 99%
“…As we have argued elsewhere (Brooks et al, 2015), there is some evidence from our research that students' unions and senior managers believed the values of the two groups were becoming increasingly aligned, largely as a result of external pressures within the HE sector.…”
Section: Students' Unions and Consumerism: A Complex Relationshipmentioning
confidence: 67%
“…Recent research on students' unions in the UK has suggested that, over the last few years, their role within the higher education (HE) sector and their relationship with their wider institution have both changed considerably (Brooks et al, 2015). Previous work has, however, tended to emphasise the political and organisational aspects of such changes.…”
Section: Introductionmentioning
confidence: 98%